2008
DOI: 10.4049/jimmunol.181.5.3243
|View full text |Cite
|
Sign up to set email alerts
|

The Suppression of Murine Lupus by a Tolerogenic Peptide Involves Foxp3-Expressing CD8 Cells That Are Required for the Optimal Induction and Function of Foxp3-Expressing CD4 Cells

Abstract: A peptide, designated human CDR1 (hCDR1), that is based on the CDR1 of an anti-DNA Ab ameliorates systemic lupus erythematosus (SLE) in murine models via the induction of CD4+CD25+ regulatory T cells (Tregs). In the present study, the involvement of CD8 Tregs in the mode of action of hCDR1 was investigated in SLE-afflicted (NZB × NZW)F1 mice and in SJL mice following immunization with the lupus-inducing anti-DNA mAb that bears a common Id, 16/6Id. Treatment with hCDR1 up-regulated Foxp3-expressing CD8+CD28− Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 40 publications
2
49
1
Order By: Relevance
“…Recent data confirmed the role of CD8 ϩ T cells in activating the suppressive program of CD4 ϩ CD25 ϩ T cells in a different mouse (C57BL/6) model (36). In the present study, we determined whether or not the same mechanism of activation of OVA-CD4 ϩ CD25 ϩ T cells occurs in BALB/c mice sensitized and challenged with the unrelated allergen RW.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Recent data confirmed the role of CD8 ϩ T cells in activating the suppressive program of CD4 ϩ CD25 ϩ T cells in a different mouse (C57BL/6) model (36). In the present study, we determined whether or not the same mechanism of activation of OVA-CD4 ϩ CD25 ϩ T cells occurs in BALB/c mice sensitized and challenged with the unrelated allergen RW.…”
Section: Discussionsupporting
confidence: 54%
“…This role for CD8 was recently supported by data suggesting that CD8 ϩ T cells enhanced the regulatory function of CD4 ϩ CD25 ϩ T cells in a different animal model (36). We investigated the effects of in vitro treatment of OVA-CD4 ϩ CD25 ϩ T cells with anti-MHC I or administration of anti-CD8␤ by microspray, before intratracheal transfer of OVA-CD4 ϩ CD25 ϩ T cells in RW sensitized and challenged mice.…”
Section: Anti-cd8 Treatment Of Recipients or Anti-mhc I Treatment Of mentioning
confidence: 83%
See 1 more Smart Citation
“…26). In previous studies, the phenotype of inhibitory CD8 Tregs was shown to fluctuate (37)(38)(39)(40). Inhibitory CD8 Treg function was reported to be defective in human SLE patients and in animal models of SLE (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…CD8 + Treg cells were first identified in human tonsils; upon in vitro activation, Foxp3 + CD8 + Treg cells were shown to inhibit T cell proliferation directly (12). CD8 + Treg cells seem to perform a regulatory function that limits autoimmune disease in several experimental models (17,31,32). Systemic immunization with allergen in mice induces CD8 + Treg cells that can inhibit the development of allergic diarrhea, suggesting that CD8 + Treg cells may play a pivotal role in limiting allergic disease (33).…”
Section: Discussionmentioning
confidence: 99%